Acceso a la justicia internacional. Una lectura transversal del Ciadi y el OSD de la OMC (2010)
This article propose some trends about the access to justice of third world states in the ICSID of the World Bank and the WTO dispute settlement mechanism. In that sense identify a group of hypothesis about opportunities and obstacles for this access taking into account an analytical framework that recognizes the particularities of international justices in comparison to national.